PCC0208009 enhances the anti-tumor effects of temozolomide through direct inhibition and transcriptional regulation of indoleamine 2, 3-dioxygenase in glioma models. (11th July 2018) - Sun, Shanyue; Du, Guangying; Xue, Jiang; Ma, Jinbo; Ge, Minmin; Wang, Hongbo; Tian, Jingwei
Indoleamine 2, 3-dioxygenase (IDO), which is highly expressed in human glioblastoma and involved in tumor immune escape and resistance to chemotherapy, is clinically correlated with tumor progression and poor clinical outcomes, and is a promising therapeutic target for glioblastoma. IDO inhibitors are marginally efficacious as single-agents; therefore, combination with other therapies holds promise for cancer therapy. The aim of this study was to investigate the anti-tumor effects and mechanisms of the IDO inhibitor PCC0208009 in combination with temozolomide. The effects of PCC0208009 on IDO activity inhibition, and mRNA and protein expression in HeLa cells were observed. In the mouse glioma GL261 heterotopic model, the effects of PCC0208009 onl -kynurenine/tryptophan (Kyn/Trp), tumor growth, flow cytometry for T cells within tumors, and immunohistochemistry for IDO and Ki67 were examined. In the rat glioma C6 orthotopic model, animal survival, flow cytometry for T cells within tumors, and immunohistochemistry for proliferating cell nuclear antigen (PCNA) and IDO were examined. The results show that PCC0208009 is a highly effective IDO inhibitor, not only directly inhibiting IDO activity but also participating in the gene regulation of IDO expression at the transcription and translation levels. PCC0208009 significantly enhanced the anti-tumor effects of temozolomide in GL261 and C6 models, by increasing the percentages of CD3 +, CD4 +, and CD8 + T cells within tumors and suppressing tumor proliferation. These findings indicate that PCC0208009 can potentiate the anti-tumor efficacy of temozolomide and suggest that combination of IDO inhibitor-based immunotherapy with chemotherapy is a potential strategy for brain tumor treatment.